Interconsulta psiquiátrica: subdiagnóstico de transtornos mentais por médicos assistentes - Machado, Mariana Aguiar (2017)
Objectives: To evaluate the frequency of liaison psychiatry (LP) consultation in a University Hospital (HU). Method: Retrospective observational study, through the analysis of medical records of patients hospitalized in the Medical and Surgical Clinics in a HU from January to December / 2015 submitted to LP. The information collected in the medical records fed a specific questionnaire (EQ) for the investigation of sociodemographic data, personal aspects and the LP performed. The analysis of the information was performed through descriptive statistics. Results: The frequency of request for LP was 3.5%, and most requests were made by Clínica Médica (71.2%), while Clínica Cirúrgica was responsible for 28.8%. The main reason for the LP request was the presence of depressive symptoms (49.1%). There was a predominance of females (52.5%) and mean age was 45.9 ± 14.6 years. The majority of the patients (62.7%) came from the capital, married or with a stable union (52.5%), with a family income of up to five minimum wages (93.2%) and autonomous labor activity in 42.4% In addition, 44.1% had incomplete elementary education. Conclusion: The frequency of LP request was very low, suggesting a difficulty in the early detection of mental disorders by the attending physicians. In view of this, it is important to note that there is a discrepancy between the percentage of LP and the high prevalence of depressive symptoms, implying an underreporting of cases.